Different effects of continuous-cover and rotation forest management on soil organic carbon stabilization in a boreal Norway spruce forest - Eva-Maria Roth; Outi-Maaria Sietiö; Bartosz Adamczyk; Pingping Xu; Sauli Valkonen; Eeva-Stiina Tuittila; Heljä-Sisko Helmisaari; Kristiina Karhu (Forest Ecology and Management, 2026)

Uneven-aged and even-aged forest management shape the soil fungal community composition in a boreal Norway spruce (Picea abies Karst) forest - Eva-Maria Roth; Outi-Maaria Sietiö; Sauli Valkonen; Eeva-Stiina Tuittila; Heljä-Sisko Helmisaari; Kristiina Karhu (Science of The Total Environment, 2025)

How do harvesting methods applied in continuous-cover forestry and rotation forest management impact soil carbon storage and degradability in boreal Scots pine forests? - Eva-Maria Roth; Kristiina Karhu; Matti Koivula; Heljä-Sisko Helmisaari; Eeva-Stiina Tuittila (Forest Ecology and Management, 2023)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Contribution to the ongoing discussion on fluoride toxicity - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2021)
Since the addition of fluoride to drinking water in the 1940s, there have been frequent and sometimes heated discussions regarding its benefits and risks. In a recently published review, we addressed the question if current exposure levels in Europe represent a risk to human health. This review was discussed in an editorial asking why we did not calculate benchmark doses (BMD) of fluoride neurotoxicity for humans. Here, we address the question, why it is problematic to calculate BMDs based on the currently available data. Briefly, the conclusions of the available studies are not homogeneous, reporting negative as well as positive results; moreover, the positive studies lack control of confounding factors such as the influence of well-known neurotoxicants. We also discuss the limitations of several further epidemiological studies that did not meet the inclusion criteria of our review. Finally, it is important to not only focus on epidemiological studies. Rather, risk analysis should consider all available data, including epidemiological, animal, as well as in vitro studies. Despite remaining uncertainties, the totality of evidence does not support the notion that fluoride should be considered a human developmental neurotoxicant at current exposure levels in European countries.

Model for leisure boat activities and emissions – implementation for the Baltic Sea - Lasse Johansson; Erik Ytreberg; Jukka-Pekka Jalkanen; Erik Fridell; K. Martin Eriksson; Maria Lagerström; Ilja Maljutenko; Urmas Raudsepp; Vivian Fischer; Eva Roth (Ocean Science, 2020)
The activities and emissions from leisure boats in the Baltic Sea have been modeled in a comprehensive approach for the first time, using a new simulation model leisure Boat Emissions and Activities siMulator (BEAM). The model utilizes survey data to characterize the national leisure boat fleets. Leisure boats have been categorized based on their size, use and engine specifications, and for these subcategories emission factors for NOx, PM2.5, CO, non-methane volatile organic compounds (NMVOCs), and releases of copper (Cu) and zinc (Zn) from antifouling paints have been estimated according to literature values. The modeling approach also considers the temporal and spatial distribution of leisure boat activities, which are applied to each simulated leisure boat separately. According to our results the CO and NMVOC emissions from leisure boats, as well as Cu and Zn released from antifouling paints, are significant when compared against the emissions originating from registered commercial shipping in the Baltic Sea. CO emissions equal 70 % of the registered shipping emissions and NMVOC emissions equal 160 % when compared against the modeled results in the Baltic Sea in 2014. Modeled NOx and PM2.5 from the leisure boats are less significant compared to the registered shipping emissions. The emissions from leisure boats are concentrated in the summer months of June, July and August and are released in the vicinity of inhabited coastal areas. Given the large emission estimates for leisure boats, this commonly overlooked source of emissions should be further investigated in greater detail.

Toxicity of fluoride: critical evaluation of evidence for human developmental neurotoxicity in epidemiological studies, animal experiments and in vitro analyses - Sabine Guth; Stephanie Hüser; Angelika Roth; Gisela Degen; Patrick Diel; Karolina Edlund; Gerhard Eisenbrand; Karl-Heinz Engel; Bernd Epe; Tilman Grune; Volker Heinz; Thomas Henle; et al. (Archives of Toxicology, 2020)
Recently, epidemiological studies have suggested that fluoride is a human developmental neurotoxicant that reduces measures of intelligence in children, placing it into the same category as toxic metals (lead, methylmercury, arsenic) and polychlorinated biphenyls. If true, this assessment would be highly relevant considering the widespread fluoridation of drinking water and the worldwide use of fluoride in oral hygiene products such as toothpaste. To gain a deeper understanding of these assertions, we reviewed the levels of human exposure, as well as results from animal experiments, particularly focusing on developmental toxicity, and the molecular mechanisms by which fluoride can cause adverse effects. Moreover, in vitro studies investigating fluoride in neuronal cells and precursor/stem cells were analyzed, and 23 epidemiological studies published since 2012 were considered. The results show that the margin of exposure (MoE) between no observed adverse effect levels (NOAELs) in animal studies and the current adequate intake (AI) of fluoride (50 µg/kg b.w./day) in humans ranges between 50 and 210, depending on the specific animal experiment used as reference. Even for unusually high fluoride exposure levels, an MoE of at least ten was obtained. Furthermore, concentrations of fluoride in human plasma are much lower than fluoride concentrations, causing effects in cell cultures. In contrast, 21 of 23 recent epidemiological studies report an association between high fluoride exposure and reduced intelligence. The discrepancy between experimental and epidemiological evidence may be reconciled with deficiencies inherent in most of these epidemiological studies on a putative association between fluoride and intelligence, especially with respect to adequate consideration of potential confounding factors, e.g., socioeconomic status, residence, breast feeding, low birth weight, maternal intelligence, and exposure to other neurotoxic chemicals. In conclusion, based on the totality of currently available scientific evidence, the present review does not support the presumption that fluoride should be assessed as a human developmental neurotoxicant at the current exposure levels in Europe.